The Impact Of Covid-19 on Homecare Workforce : An Analytical Review - Edison Kabak; Nuriati Sarlota Auparai; Yoel Halotopo (Jurnal Berita Ilmu Keperawatan, 2023)
The prevalence of Covid-19 patients’ visits at health care centers in the past one and a half years has resulted in an increase in the need for a nurses workforce. Ironically, on the other hand, there is a decrease in the demand and supply of homecare nurses. This study aims to explore the impact of Covid-19 on homecare nurses and offer solutions in the form of maximizing the role of homecare nurses in the pandemic era by using a document review. The study used an analytical review with a descriptive design. The literature was drawn from Google Scholar, ResearchGate, Pubmed, SagePub, and Semantic Scholar. With the PRISMA analysis strategy, the documents in the database (n=160), which deserve to be reviewed (n=47), and those that meet the requirements for review (n=10). The output: the pandemic caused a shortage of nurses and a moderate level of stress among nurses, where agencies experienced a decrease in demand for homecare nurses. The conclusion of this research is to maximize the role of homecare nurses in the pandemic era, it is necessary to have specific guidelines or protocols regarding COVID-19 prevention and management of homecare or for a long-term care system.